The Racism of The Black Women in Audre Lorde Selected Poems Entitle Power, Who Said It Was Simple, and A Woman Speaks - Lady Lady; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2021)
This study aims to describe the racism reflected in the poems entitled Power, ‘Who Said It Was Simple and A Woman Speaks, and to reveal the power of black women against racism in Audre Lorde's poems entitled Power, Who Said It Was Simple and A Woman Speaks. The method used in the collection is the documentation method because the writer collected data from the poems. Data collection was carried out by reading the poem in a comprehensive manner to understand its entire content and find the meaning, especially the essence associated with the topic, identifying data which could be a sentence, then the data object can be separated from each stanza and found the value of racism on each line of poetry, after knowing the results of the analysis the writer will draw conclusions. While the data analysis steps the writer uses critical race theory by Delgado and Stefancic (2001), such as: racism, race and power. Second, identifying the power of black women by utilizing the concept of Black Feminist by Collins (2000), and the Black Power Movement edited by Joseph (2006), then the writer interprets the data, the final step is to draw conclusions. The author can draw some conclusions that the 3 types of poetry are classified into satire and are written based on the reality that occurs in the author’s experience. In the poem 'Power', there are several aspects of racism, namely skin colour, injustice, segregation and racial discrimination. From the poem 'Who Said It Was', there are aspects of racism, such as gender, skin colour, and homophobia. In poem 'A woman speak’ there are several aspects of racism contained in poetry, namely discrimination against race, sex, and skin colour. Apart from racist values, the three poems also contained ‘The Power of Black Women’ or what is called the power or means used by women to fight racism.